Palmoplantar pustular psoriasis: an update on pathophysiology and review of treatment options (Canadian Dermatology Today, 2022)
Palmoplantar pustular psoriasis (PPPP) is a localized variant of pustular psoriasis that does not respond predictably to conventional psoriasis treatments and is a notoriously challenging condition to manage even though it shares many clinical and histopathologic features with plaque psoriasis. This review will briefly explore the clinical and pathophysiological features of PPPP and look at the evidence behind treatment of this condition using systemic and advanced therapies.